2019
DOI: 10.1111/jedm.12258
|View full text |Cite
|
Sign up to set email alerts
|

Using Weighted Sum Scores to Close the Gap Between DIF Practice and Theory

Abstract: We make a distinction between the operational practice of using an observed score to assess differential item functioning (DIF) and the concept of departure from measurement invariance (DMI) that conditions on a latent variable. DMI and DIF indices of effect sizes, based on the Mantel-Haenszel test of common odds ratio, converge under restricted conditions if a simple sum score is used as the matching or conditioning variable in a DIF analysis. Based on theoretical results, we demonstrate analytically that mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…First, we define the terms DIF and DMI used in this study, and then we illustrate MH DIF statistics with simple sum scores as the matching variable and MH DIF statistics matched with the weighted sum scores, using three different binning methods. Note that the definitions or calculations are consistent with Guo and Dorans (2019, 2020). For more discussion of these definitions, please refer to Guo and Dorans (2019, 2020).…”
Section: The Mh Dif Statisticssupporting
confidence: 72%
See 4 more Smart Citations
“…First, we define the terms DIF and DMI used in this study, and then we illustrate MH DIF statistics with simple sum scores as the matching variable and MH DIF statistics matched with the weighted sum scores, using three different binning methods. Note that the definitions or calculations are consistent with Guo and Dorans (2019, 2020). For more discussion of these definitions, please refer to Guo and Dorans (2019, 2020).…”
Section: The Mh Dif Statisticssupporting
confidence: 72%
“…Recently, Guo and Dorans (2019, 2020) made a distinction between DIF and DMI, in which DIF is defined as the statistics that are based on observed scores to assess items' differential performance across different groups of test takers, and DMI is defined as the departure from measurement invariance based on the measured latent ability. Guo and Dorans (2019, 2020) proposed the use of weighted sum scores (where weights are equal to the estimated discrimination parameters) in the DIF context. Through analytic methods, they showed that the DIF indices of effect sizes are different from the DMI measure under the 2PL model in many situations when a simple sum score is used as the matching or conditioning variable in DIF analysis.…”
mentioning
confidence: 99%
See 3 more Smart Citations